A Combined 1H/6Li NMR DOSY Strategy Finally Uncovers the Structure of Isopropyllithium in THF. Issue 51 (9th August 2017) - Barozzino‐Consiglio, Gabriella; Hamdoun, Ghanem; Fressigné, Catherine; Harrison‐Marchand, Anne; Maddaluno, Jacques; Oulyadi, Hassan
Abstract: Despite its common use in synthesis, the structure of isopropylliyhium in THF has never been determined, a dimer being generally proposed but not supported. This paper fills this data gap through a sophisticated NMR study that shows that, in THF at low‐temperature, isopropyllithium is in the form of a 1:2 mixture of a trisolvated monomer and a disolvated dimer in equilibrium. The presence of the monomer, never evoked before, together with a hypo‐solvation of the dimer hinted by DFT calculations, provides a rational explanation to the remarkable reactivity of this organolithium reagent in ethereal solvents. Abstract : Spotting a stowaway ! Our NMR+DFT results demonstrate that, in cold THF, isopropyllithium adopts two structural arrangements; a trisolvated monomer and a disolvated dimer, in a 1:2 ratio. The occurrence of a monomeric solvate, never observed before, helps to understand the high reactivity of this commodity reagent.